When opportunistic predators interact with swordfish harpoon fishing activities: shark depredation over catches in the Strait of Messina (central Mediterranean Sea). Issue 1 (1st January 2021) - Malara, D.; Battaglia, P.; Consoli, P.; Arcadi, E.; Longo, F.; Stipa, M. G.; Pagano, L.; Greco, S.; Andaloro, F.; Romeo, T.
Abstract: We describe the interaction between harpoon fishing activity and sharks, which opportunistically depredated harpoon catches in the Strait of Messina. Shark bite marks were observed on harpooned swordfish during the period 2014–2020, with different damages to the catches. Most of the depredation events have focused on large swordfish, generally weighing more than 60 kg. Data on direct observations were implemented by interviews and questionnaires to fishermen aimed to recover the information on their local fishing and ecological knowledge. Fishermen provided additional data on shark-harpoon fishing interactions also supplying information on by-catch species (i.e., bluefin tuna). Therefore, these results suggest that sharks migrating through the Strait of Messina are occasionally attracted by injured prey, due to their ability to detect chemical cues, fish distress stimuli and body fluids (i.e. blood) in the water. In addition, our investigations showed an increase in shark attacks on harpooned fish over time, likely due to an increase in harpoon swordfish catches. This may be related to the effects of the driftnets' ban enforced by European Regulations in the last decades.